2016
DOI: 10.1152/jn.01069.2015
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the inferior olive prevents H-reflex down-conditioning in rats

Abstract: We evaluated the role of the inferior olive (IO) in acquisition of the spinal cord plasticity that underlies H-reflex down-conditioning, a simple motor skill. The IO was chemically ablated before a 50-day exposure to an operant conditioning protocol that rewarded a smaller soleus H-reflex. In normal rats, down-conditioning succeeds (i.e., H-reflex size decreases at least 20%) in 80% of animals. Down-conditioning failed in every IO-ablated rat (P Ͻ 0.001 vs. normal rats). IO ablation itself had no long-term eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…None of CST transection, DIN ablation or IO ablation has a long-term effect on H-reflex size in naïve (i.e. unconditioned) rats (Chen et al 2001(Chen et al , 2016a. Thus, the effects in Fig.…”
Section: A Simple Motor Behaviour: the Reflex Operant Conditioning mentioning
confidence: 77%
See 1 more Smart Citation
“…None of CST transection, DIN ablation or IO ablation has a long-term effect on H-reflex size in naïve (i.e. unconditioned) rats (Chen et al 2001(Chen et al , 2016a. Thus, the effects in Fig.…”
Section: A Simple Motor Behaviour: the Reflex Operant Conditioning mentioning
confidence: 77%
“…If the IO is ablated before down‐conditioning, the H‐reflex does not decrease; if it is ablated after down‐conditioning, some of the decrease disappears over 10 days while the remainder survives for 40 days and then disappears (Chen et al . 2016 a , b ). The gradual partial loss of the H‐reflex decrease after IO ablation compared to the immediate partial loss after DIN ablation suggests that the IO guides cerebellar plasticity that survives 10 days without continued IO influence.…”
Section: Evidence Supporting the Modelmentioning
confidence: 99%
“…They have shown that such conditioning produces multisite changes at the level of the spinal cord that drive the observed differences in the H-reflex response, including a shift in motorneuron firing threshold [76] and a change in the number of GABAergic terminals [77]. Importantly, successful operant conditioning of the spinal cord circuit itself requires a functional corticospinal tract and sensorimotor cortex as well as the cerebellum and inferior olive but no other major ascending or descending spinal pathways [78][79][80][81][82][83][84], indicating that cerebellar contributions by the sensorimotor cortex (as opposed to the rubrospinal tract) are critical for implementing learning [80,81]. Given the differences between H-reflex operant conditioning, especially with respect to its development over weeks and months, an extremely long timescale even relative to the slow learning in our paradigm, it is unclear whether the same mechanisms are in play for the type of learning we report here.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that such conditioning produces multisite changes at the level of the spinal cord that actually drive the observed differences in the H-reflex response, including a shift in motorneuron firing threshold (Carp and Wolpaw, 1994) and a change in the number of GABAergic terminals (Wang et al, 2006) . Importantly, successful operant conditioning of the spinal cord circuit itself requires a functional corticospinal tract and sensorimotor cortex as well as the cerebellum and inferior olive but no other major ascending or descending spinal pathways Wolpaw, 2002, 2005;Chen et al, , 2006aChen et al, , 2006bChen et al, , 2016Wolpaw and Chen, 2006) , indicating that cerebellar contributions via the sensorimotor cortex (as opposed to the rubrospinal tract) are critical for implementing the learning (Chen and Wolpaw, 2005;Wolpaw and Chen, 2006) . Given the differences between H-reflex operant conditioning, especially with respect to its development over weeks and months, an extremely long time-scale even relative to the slow learning in our paradigm, it is unclear whether the same mechanisms are in play for the type or learning we report here.…”
Section: Internal Models For Feedback Controlmentioning
confidence: 99%